THE FAILURE OF EXTREME CAPITALISM : IS ISLAMIC ECONOMICS THE ANSWER? - Muhammad Hisyam Mohamad; Nur Syahidah Abdul Jalil (Khayra Ummah Series (No.5/9), 2022)
This volume is part of the Khayra Ummah series, being itself the culmination of a sequence of colloquium of several themes organised by IKIM. The issues addrressed in this series are : Islamic economics; Islamophobia;governance;moral deterioration;disruptive technology;the Islamic state and society; environmental degradation; and the Islamic mind.